Fenomena Sewa Rahim (Surrogate Mother) dalam Perspektif Hukum dan Hak Asasi Manusia di Indonesia - Raida Rhumaisha (CV. ULIL ALBAB CORP, 2024)
Every couple has a dream of having children, but it is undeniable that there is a certain condition where the wife cannot conceive due to an abnormality in her womb or another cause that causes the wife to be unable to conceive. Advances in medical technology have made this problem a solution, for example by artificial fertilization or through in vitro fertilization (IVF) technology known as IVF. In its growth, the IVF program has progressed by being carried out through a surrogate mother. However, due to the practice of renting a uterus, new problems arise in the fields of law and religion. This study focuses on the legal status of uterine rental in Indonesia and around the world as well as how legal guarantees are provided for children and surrogate mothers. The results of the analysis and discussion found that the study of uterine rental was not in accordance with the principles of Islamic law. This is regulated in Law No. 23 of 1992, as well as a fatwa issued by the Indonesian Ulema Council on May 26, 2006. Seen in Article 12 of Law No. 36 of 2009 concerning Health, it contains the law on the implementation of IVF practice. The practice of surrogation, if pursued through moral policies, is considered contrary to human values, especially according to the European Centre for Law and Justice in 2012 that using surrogacy is an act that violates humanitarian principles because it exploits women and children and makes them a business commodity.